Research of changes in electromagnetic parameters in controlled asynchronous special electric drives - V. Yu. Karandey; O. B. Popova; B. K. Popov; V. L. Afanasiev (Омский научный вестник)
The article researches the changes in the electromagnetic parameters of controlled asynchronous special electric drives. Special asynchronous electric drives are controlled cascade electric drives of cylindrical and axial designs. The study of the dynamics of parameter changes is carried out on the basis of the method of electromagnetic energy conversion and the theory of electromagnetic circuits. As a result, for new mathematical models of the electromagnetic system of the studied asynchronous electric drives, the parameters of the electromagnetic field of a closed coil of one coil of an electric winding with electric current in a homogeneous medium are determined. The solved problem is spatial, since the distribution of electromagnetic induction in a coil of a given shape of an electromagnetic coil is determined. The obtained conclusions for determining the electromagnetic parameters of cylindrical and axial motors of special electric drives allow us to correctly solve the problems of modeling, designing and improving the efficiency of the studied electric drives and electromechanical energy converters of cylindrical and axial designs. The results of the study are applicable to create a computer-aided design system for the research asynchronous electric drives and solve modeling and design problems. The conducted research allows creating electric drives with optimal weight, size and energy indicators.